Evaluation of an E‐learning resource on approach to the first unprovoked seizure. (20th September 2016) - Le Marne, Fleur A; McGinness, Hannah; Slade, Rob; Cardamone, Michael; Balbir Singh, Shirleen; Connolly, Anne M; Bye, Ann ME
Abstract : Aim: To develop and evaluate an online educational package instructing paediatricians and trainees in the diagnosis and management of a first unprovoked seizure in children. Methods: The E‐learning content was created following a comprehensive literature review that referenced current international guidelines. Rigorous consultation with local paediatric neurologists, paediatricians and epilepsy nurses was undertaken. A series of learning modules was created and sequenced to reflect steps needed to achieve optimal diagnosis and management in a real‐life situation of a child presenting with a paroxysmal event. Paediatric registrars and advanced trainees from the Sydney Children's Hospitals Network were assessed before and after using the E‐learning Resource. Measures included general epilepsy knowledge, case‐based scenario knowledge; self‐rated measures of satisfaction with instruction and confidence regarding clinical approach to the child with first unprovoked seizure; and open ended questions evaluating the usefulness of the E‐learning resource. Results: Performance on measures of general epilepsy knowledge and on the seizure‐related case scenarios improved significantly following completion of the E‐learning as did self‐rated satisfaction with instruction and confidence across all aspects of managing first seizure. Conclusions: The E‐learning resource has been validated as a useful educational resource regarding the first afebrile unprovoked seizure for paediatricians.